2016
DOI: 10.1002/hbm.23357
|View full text |Cite
|
Sign up to set email alerts
|

Altered cortical beta‐band oscillations reflect motor system degeneration in amyotrophic lateral sclerosis

Abstract: Continuous rhythmic neuronal oscillations underpin local and regional cortical communication. The impact of the motor system neurodegenerative syndrome amyotrophic lateral sclerosis (ALS) on the neuronal oscillations subserving movement might therefore serve as a sensitive marker of disease activity. Movement preparation and execution are consistently associated with modulations to neuronal oscillation beta (15–30 Hz) power. Cortical beta‐band oscillations were measured using magnetoencephalography (MEG) durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
61
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 138 publications
(162 reference statements)
12
61
1
Order By: Relevance
“…Additionally, neuropathological studies have shown prominent and consistent CC involvement in ALS, most abundant in the middle part 16 17. Neuroelectrophysiological studies such as TMS and MEG have also provided indirect evidence of impaired CC functioning by showing alterations of interhemispheric inhibition18 and cortical β-band oscillations 19. Based on these structural and functional alterations of CC, the present study complemented/extended these previous studies by showing a compromised interhemispheric neural connectivity.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, neuropathological studies have shown prominent and consistent CC involvement in ALS, most abundant in the middle part 16 17. Neuroelectrophysiological studies such as TMS and MEG have also provided indirect evidence of impaired CC functioning by showing alterations of interhemispheric inhibition18 and cortical β-band oscillations 19. Based on these structural and functional alterations of CC, the present study complemented/extended these previous studies by showing a compromised interhemispheric neural connectivity.…”
Section: Discussionsupporting
confidence: 83%
“…The observed changes in spectral power are consistent with previously described θand α-band power decrease above the sensorimotor network (Bizovi car, Dreo, Koritnik, & Zidar, 2014;Nasseroleslami et al, 2019). Other studies in ALS have similarly identified decreased postmovement β-band power above motor cortices (Proudfoot et al, 2017;Riva et al, 2012), which is considered a reflection of idling and/or an active inhibition of the motor network (Cassim et al, 2001).…”
Section: Spectral Power Changes In Als Diseasesupporting
confidence: 90%
“…Note that the widespread patterns of increased co-modulation [amplitude envelope correlation (AEC)] are predominantly in the θand γ l -bands, while synchrony [imaginary coherence (iCoh)] patterns were predominantly in the δand β-bands. Other studies in ALS have similarly identified decreased postmovement β-band power above motor cortices (Proudfoot et al, 2017;Riva et al, 2012), which is considered a reflection of idling and/or an active inhibition of the motor network (Cassim et al, 2001). False discovery rate (FDR) was set to 10% (in each frequency band), yielding an estimated statistical power of 1-β = .96 and posterior probability of P 1 = .56 in the θ-band AEC and an estimated statistical power of 1-β = .89 and posterior probability of P 1 = .7 in the γ l -band AEC.…”
Section: Spectral Power Changes In Als Diseasementioning
confidence: 76%
“…Even though this latest finding seems in contrast with a recent MEG study30 that reported an intensified cortical beta desynchronization in ALS patients, other studies have not reported the same finding2831. Differences in protocol design, for example the use of different tasks, or resting-state data, or differences in characteristics of the patient population, may explain these differences across studies.…”
Section: Discussionmentioning
confidence: 57%